FoxO3a suppression and VPS34 activity are essential to anti-atrophic effects of leucine in skeletal muscle - Baptista, Igor L.; Labeit, Siegfried (Cell & tissue research, 2017)
Our aim is to gain insight into the mechanisms underlying the anti-atrophic effects of leucine, namely, the way that this amino acid can restrain the up-regulation of MuRF1 and Mafbx/Atrogin-1 in muscle atrophy. Male rats received dietary leucine supplementation for 1-3 days, during which time their hind limbs were immobilized. Our results showed that leucine inhibited Forkhead Box O3 (FoxO3a) translocation to cell nuclei. In addition, leucine was able to reverse the expected reduction of FoXO3a ubiquitination caused by immobilization. Unexpectedly, leucine promoted these effects independently of the Class I PI3K/Akt pathway. Vacuolar protein sorting 34 (VPS34; a Class III PI3K) was strongly localized in nuclei after immobilization and leucine supplementation was able to prevent this effect. In experiments on cultured primary myotubes, dexamethasone led to the localization of VPS34 in the nucleus. In addition, the pharmacological inhibition of VPS34 blocked VPS34 nuclear localization and impaired the protective effect of leucine upon myotube trophicity. Finally, the pharmacological inhibition of VPS34 in primary myotubes prevented the protective effects of leucine upon MuRF1 and Mafbx/Atrogin-1 gene expression. Autophagy-related target genes were not responsive to leucine. Thus, we demonstrate that the anti-atrophic effect of leucine is dependent upon FoxO3a suppression and VPS34 activity.